Vaccine hesitancy in South Tyrol: a narrative review of insights and strategies for public health improvement - Wiedermann, Christian J.; Barbieri, Verena; Plagg, Barbara; Piccoliori, Giuliano; Engl, Adolf (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. This review examines vaccine hesitancy in South Tyrol, Italy, a region characterized by cultural and linguistic diversity. The critical need for vaccination to control infectious diseases contrasts with the region’s low vaccination rates, which pose a significant public health challenge.Methods. Based on literature, reports, and studies, we used PubMed, Embase, and Google Scholar to explore vaccine hesitancy in South Tyrol. It emphasizes the analysis of historical, cultural, and socioeconomic factors, and focuses on quantitative surveys and qualitative interviews to understand the roots of vaccine hesitancy.Results. In two studies with four reports, mistrust in health policies and institutions, misinformation, and cultural and linguistic barriers were identified as key factors contributing to vaccine hesitancy in South Tyrol. These factors are accentuated by the region’s unique sociopolitical landscape, which influences public health policies and vaccination initiatives.Conclusions. These findings highlight the need for public health strategies specifically tailored to South Tyrol. Recommended actions include developing culturally sensitive and multilingual communication campaigns, increasing community involvement, and rebuilding trust in healthcare systems. These approaches are essential for addressing the specific challenges in South Tyrol, thereby improving vaccine uptake and overall public health outcomes.